Ortognaisses peraluminosos associados ao Grupo Araxá na região de Mairipotaba-Prof. Jamil Safady, Goiás - Navarro, Guillermo Rafael Beltran; Zanardo, Antenor; Conceição, Fabiano Tomazini Da (Sociedade Brasileira de Geologia, 2014)
Several gneissified granitic bodies occur in the southern region of Goiás State, Brazil, hosted in metasedimentary sequences of the Araxá Group. Two of these rock bodies are located in the outskirts of Mairipotaba and Cromínia, Professor Jamil Safady District, and display peraluminous, calc-alkaline compositions, been classified as S-type. These granitic bodies show low to medium content of alkali, large ion lithophile elements enrichment (Cs, Th, U, Ba, Rb, K) and light rare earth elements in relation to heavy rare earth elements and to high field strength elements (Zr, Y, Nb, Ta, Hf). They also exhibit negative anomalies of Nb, Ta, P and Ti, similar to the chemical composition of magmas originated in magmatic arcs. Geochemical comparison between these rocks and the metasediments of the Araxá Group, in accordance to the geological context, indicates that the sources of the magma that originated these granitic bodies are metasediments from the Araxá Group.

Na região sul de Goiás ocorrem numerosos corpos graníticos gnaissificados alojados nos metassedimentos do Grupo Araxá. Duas dessas ocorrências estão localizadas nos arredores dos municípios de Mairipotaba e Cromínia, na cidade de Professor Jamil Safady. Essas duas ocorrências têm composição peraluminosa, cálcio-alcalina e são classificadas como do tipo-S. Esses corpos graníticos apresentam baixos a médios teores de álcalis, enriquecimento em elementos litófilos de raio iônico grande (Cs, Th, U, Ba, Rb, K) e ETRL em relação a ETRP e a elementos de alto campo de força (Zr, Y, Nb, Ta, Hf). Apresentam ainda anomalias negativas de Nb, Ta, P e Ti, semelhantes à composição química de magmas gerados em arcos magmáticos. A comparação geoquímica das amostras desses ortognaisses com metassedimentos do Grupo Araxá, em congruência com o contexto geológico, mostra que a fonte dos magmas dos corpos graníticos são os metassedimentos pertencentes ao Grupo Araxá.
Peraluminous orthogneiss associated whit the Araxá Group in the region of Mairipotaba-Prof. Jamil Safady, Goiás
Keywords: Faixa Brasília; Grupo Araxá; geoquímica; Brasília Belt; Araxá Group; geochemistry